Assessment of spatial suitability of ecotourism sites in Al-Ahsa governorate, Saudi Arabia, by using GIS - Al-Balawi, Amal Bashir; Ouerghi, Sarra Al-Habib (Journal of Humanities & Social Sciences, 2022)
The study assessed the spatial suitability of the natural ecotourism sites in Al-Ahsa governorate in Saudi Arabia, through this assessment, the study aimed to identify the components of ecotourism sites in the study area at an initial step and, at a second step, produce maps that would determine their spatial suitability for ecotourism using GIS technology. Based on a series of steps and process, the study began with the construction of a geographic database of the region's tourism natural resources that reached the number of 21 sites, which have been extracted from various data sources. After this step criteria of spatial suitability of the natural ecotourism sites have been defined and selected Based on standards of the Ministry of Municipal Rural Affairs and housing, standards of the Saudi commission for Tourism and National Heritage and standards derived from literary references. These criteria consisted of a natural and human standard that have a direct impact on the success of a tourist site. On the basis of this, twelve criteria have been identified and represented in the form of layer, which have been merged, after assigning a weight to each criterion according to its importance, with each other through the overlay mechanism and produce a map identifying suitable sites for natural environment tourism in the study area. Through this map, the study area is characterized by the existence of ecotourism sites, meeting the requirements and standards of environmental tourism sites, according to three levels of suitability (High, medium, low). 10 sites show a high level of suitability for ecotourism from a total of 21 sites which represents 48% of all sites. while the number of sites with a medium suitability level reached the number of 2 sites, representing 9.5% of all sites. Sites that show the low suitability are 7 sites, which represents 33% of all sites. Through those findings, some recommendations have been proposed, the most important which were: taking care of the ecotourism sites identified in the study area; taking greater care to the infrastructure, especially roads, to ensure easy access to these environmental tourism sites; Adoption of an effective strategy for creating and distributing services near these sites; and finally highlight them to tourists through marketing in tourism guides and programs and the web mapping.
Keywords: Al-Ahsa region; ecotourism; geographic information systems; spatial adequacy